504 ANALYSIS OF NUCLEOCYTOPLASMIC DISTRIBUTION OF THE ONCOPROTEIN SKIN IN HUMAN ALVEOLAR RHABDOMYOSARCOMA CELLS BY IMMUNOELECTRON MICROSCOPY. Issue 1 (1st January 2007) - Brown, J.; Howard, T.; Reinert, B.; Bear, D.
Abstract : The Ski oncoprotein functions as a transcriptional corepressor in transforming growth factor β signaling, regulating cellular proliferation, differentiation, and development for several tissues, including skeletal muscle. Multiple human cancers overexpress Ski, which may play a part in malignant cellular transformation. This research focuses on Ski subcellular localization in rhabdomyosarcoma, a pediatric muscle cell cancer. Quantitative analysis of the cellular distribution of the oncoprotein Ski in a rhabodomyosarcoma cell line and a normal human skeletal muscle cell line shows a denser nuclear than cytoplasmic distribution in both cell lines. This analysis shows a significant difference ( p = .013) in the nuclear to cytoplasmic ratio of Ski between skeletal muscle cells (mean = 1.38) and rhabodomyosarcoma cells (mean = 2.06). Likewise, there is a significant difference in the fractional distribution to nuclear and cytoplasmic Ski ( p = .017), with a skeletal muscle cell line mean of 0.56 and a mean distribution in the rhabdomyosarcoma cell line of 0.65. This indicates that there is a significant quantitative difference between normal skeletal muscle cells and rhabodomyosarcoma cells in the intracellular distribution of the oncoprotein Ski that trends toward nuclear staining.